Approaching the Leper Colony, Trinidad. - (:unkn) unknown (My University, 2010)
Photo of Leper Colony in Trinidad and Tobago.
Colour: White, Brown and Cream Hues ; Style: Landscape ; Other: Bordered, Undivided.
Keywords: Trinidad and Tobago; Postcards; Chacachacare Island; Leprosy--Patients; Islands--Trinidad and Tobago